2004
DOI: 10.1212/01.wnl.0000142043.32578.5d
|View full text |Cite
|
Sign up to set email alerts
|

CSF nitric oxide metabolites are associated with activity and progression of multiple sclerosis

Abstract: CSF nitrite and nitrate levels were increased in mildly disabled patients with MS and found to correlate with the volume of Gd-enhanced lesions on MRI. Raised baseline CSF NOx was associated with clinical and MRI progression in MS patients over 3-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
66
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 45 publications
5
66
0
2
Order By: Relevance
“…The partial reduction of NO (4) and TNF-a (5) synthesis prevents the development of EAE. Furthermore, NO metabolites detected in the cerebrospinal fluid of MS patients are associated with the progression of the disease (6). These data indicate an important role of NO and TNF-a in the onset of MS.…”
mentioning
confidence: 69%
“…The partial reduction of NO (4) and TNF-a (5) synthesis prevents the development of EAE. Furthermore, NO metabolites detected in the cerebrospinal fluid of MS patients are associated with the progression of the disease (6). These data indicate an important role of NO and TNF-a in the onset of MS.…”
mentioning
confidence: 69%
“…Nitric oxide is difficult to be measured directly and NO level is mainly measured by its nitroderivatives in CSF or peripheral plasma. Several immunohistochemical studies have shown 1.5 to 3 times higher NO endproducts levels in MS patients compared with controls (Acar et al, 2003;Rejdak et al, 2004) and such increased NO can be diffuse and distal to the lesions (Moncada and Bolanos, 2006;Smith and Lassmann, 2002). Although it is difficult to differentiate these two pathological processes in vivo using our techniques, we note that the CMRO 2 reduction in MS patients was about 20% (compared with control subjects), which was much greater than the atrophic change (B2%) or lesion volume (B0.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebrospinal fluid (CSF) studies have confirmed the findings of increased inflammation, 13,14 axonal damage, 15,16 demyelination 17 and oxidative stress 18,19 in progressive MS. However, to our knowledge no studies have explored whether these CSF biomarkers are related in progressive MS. On this background we hypothesised that biomarkers of inflammation, axonal damage and demyelination are increased in secondary progressive MS (SPMS) and primary progressive MS (PPMS) and that these biomarkers correlate.…”
Section: Introductionmentioning
confidence: 88%